Turkey : Financial Sector Assessment Program: detailed assessment of Observance-Assessment of Observance of the CPMI-IOSCO Principles for Financial Market Infrastructure. (IMF Staff Country Reports; Country Report ;, 2017)
This paper presents an assessment of observance of the CPMI-IOSCO (Committee on Payments and Market Infrastructures-International Organization for Securities Commissions) principles for financial market infrastructures in Turkey. The electronic funds transfer system in Turkey broadly observes the risk management framework and liquidity risk management, default management, and operational risk management principles. It partially observes the tiered participation principle. The rest are observed or not applicable. The electronic securities transfer system broadly observes the risk management framework, liquidity, default management, and operational risk principles; the rest are observed or not applicable.